Assessing the Ergonomic and Anthropometric Challenges of the Potters Community: A Case of Pottery Town, Bengaluru - Rajashree. P. Babladi; Nalini N. S.; Vidhya M. S. (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Pottery and statue-making are physically demanding crafts involving prolonged sitting postures, repetitive movements, and exposure to environmental conditions. These craftsmen tend to suffer from musculoskeletal disorders because of poor workspace ergonomics. This study aims to evaluate the ergonomic and anthropometric problems encountered by the potters' community of Pottery Town, Bengaluru. The research used qualitative and quantitative methods, focusing on observation, survey, and documentation of artisan activities. Data was collected from field visits, ergonomic examination, and interviews involving stakeholders, which included potters, statue makers, and physiotherapists. Observation of the posture recording, patterns of work, and the use of space in the pottery workshops in Pottery Town. A subjective questionnaire survey was conducted for twenty potters, fifteen statue makers, and five physiotherapists. The questions addressed discomfort areas, work duration, and workspace adequacy. Documentation was made with photographic and sketch-based mapping of existing workspaces. The study confirms that both potters and statuemakers experience significant discomfort, especially in the lower back (72%), neck and shoulders (58%), and wrists, due to awkward postures and repetitive strain. Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) scores averaged between 5–9, indicating medium to high risk. According to the World Health Organization (WHO) and ergonomic standards, RULA scores of 5–6 require prompt changes, while 7+ indicates urgent intervention. REBA scores of 5–7 suggest medium risk, and 8-10 denote high risk, needing immediate redesign. Inadequate lighting (65%) and poor seating (80%) further contribute to fatigue and reduced precision, highlighting the need for urgent ergonomic intervention.